PENGEMBANGAN USAHA BUDI DAYA IKAN NILA (OREOCHROMIS NILOTICUS) DENGAN POLA KEMITRAAN DI KELOMPOK PEMBUDIDAYA IKAN REBAN BATU DESA LENEK - Mohammad Subhan; Rasyid R Hamidy; Abdul Majid Junaidi (Universitas Mataram, 2023)
Tilapia (Oreochromis niloticus) is an important economic fish with an easy cultivation process, popular taste, relatively affordable price and wide tolerance to the environment. The ratio of tilapia fish farming business in Lenek Village has more than one so that the tilapia fish farming is worth to develop. The Management of groups are not working, the technology of production is still conventional, the price of feed is high and the unstable market access greatly affect the sustainability of tilapia farming business. The objectives of PKM activities are: 1) implementing group facilitation and administration assistance, 2) implementing technology production facilitation and assistance, and 3) implementing feed and market partnership facilities and assistance. Implementation methods used in the realization of science and technology include counseling, training and mentoring. The Inti Plasma partnership pattern method is used in the implementation of this PKMS, in which the relation of partnership between the fish cultivator is the plasma and the company or partner has the role of providing production facilities such as feed. The result of this PKMS activities is that the Reban Batu Fish Farmers Group is able to carry out the administration, innovative technology applications and build partnership networks. The Partner Group was able to establish an access of feed partnership with BUMDES Lomboq Buaq. Marketing of Terjalis fish production partnership with UD. Arzi. This PKMS activities has had an impact on the Reban Batu Fish Farmers Group as a group of partners in understanding the goals and experiencing the benefits of carrying out group administration activities, experiencing increased production with the application of aquaculture technology, establishing partnerships related to the access of feed and markets